Kampanye Energi Terbarukan (Renewable Energy) di Lingkungan Penerbangan bagi Siswa SMA/SMK - Kona, Musri; Palpialy, Jemi Victor; Bunahri, Rifqi Raza (Darmabakti: Jurnal Inovasi Pengabdian dalam Penerbangan, 2024)
Urgent items (such as important components or easily damaged items) and/or valuable items are usually sent via air transportation. To support air transportation, airports must have adequate facilities such as consistent and more efficient electricity flow so that the use of renewable energy in the aviation industry continues to develop. This community service used a literature review method by conducting a literature review. The purpose of this community service is to teach or introduce to students that renewable energy, such as solar energy, if utilized properly in the world of aviation, will produce a very useful innovation, such as oil substitute fuel for aircraft, which is certainly more affordable so that operational costs will also be more efficient. The results of this community service were to teach and introduce to students that renewable energy, such as biomass energy, will produce very useful innovations, such as fuel oil substitutes for aircraft, which are cheaper and more efficient in the Aviation Environment for SMA/SMK Students in Jayapura.